1999
DOI: 10.1097/00004032-199903000-00005
|View full text |Cite
|
Sign up to set email alerts
|

MICRONUCLEUS FREQUENCY AND CELL PROLIFERATION IN HUMAN LYMPHOCYTES EXPOSED TO 50 Hz SINUSOIDAL MAGNETIC FIELDS

Abstract: In the present study micronucleus induction and cell proliferation in human peripheral blood lymphocytes cultured in vitro and exposed to 50 Hz sinusoidal magnetic fields for 72 h at different intensities (1.0, 0.75, 0.5, 0.25, and 0.05 mT rms) were investigated. The results obtained from 42 healthy donors aged between 26 and 54 y indicate that, for the field intensities tested, no genotoxic effects were found, as assessed by the cytokinesis-block micronucleus assay. On the contrary, cell proliferation, evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 0 publications
2
14
0
Order By: Relevance
“…The incidence of MN was not affected in cells obtained from healthy individuals and also in subjects with Turner's syndrome (TS). In a subsequent study, Scarfi et al [1999] used Helmholtz coils (80 turns of double wrapped 2 mm copper wire, 21 cm diameter) to generate sinusoidal MF. At several flux densities, the absence of an increase in MN was confirmed in cells from a larger number of healthy donors.…”
Section: Chromosomal Aberrations (Ca) Micronuclei (Mn) and Sister Cmentioning
confidence: 99%
“…The incidence of MN was not affected in cells obtained from healthy individuals and also in subjects with Turner's syndrome (TS). In a subsequent study, Scarfi et al [1999] used Helmholtz coils (80 turns of double wrapped 2 mm copper wire, 21 cm diameter) to generate sinusoidal MF. At several flux densities, the absence of an increase in MN was confirmed in cells from a larger number of healthy donors.…”
Section: Chromosomal Aberrations (Ca) Micronuclei (Mn) and Sister Cmentioning
confidence: 99%
“…At the end of the culture period (72 h growth), cells were harvested and were mounted on slides, fixed and stained with Giemsa as described elsewhere (14). After gentle homogenization of the cell suspension, 1 ml of the cell culture was centrifuged and 3 ml of lysis buffer (10 mM EDTA, 155 mM NH 4 Cl and 10 mM KHCO 3 ) was added to the cell pellet for 7 min at room temperature to break the erythrocytes.…”
Section: Cell Culture and Micronucleus Assaymentioning
confidence: 99%
“…Khalil and Qassem [1991], on the other hand, observed a reduction of cell proliferation in human lymphocytes exposed to pulsed EMFs (50 Hz, 1.05 mT). Scarfì et al [1999] reported an increase of cell proliferation in terms of cytokinesis block proliferation index (CBPI) in human lymphocytes exposed to ELFMFs (50 Hz 1 mT) and a decrease in cells exposed to 0.05 mT, supporting the idea that the direction of the effect can be changed according to different exposure conditions. Finally, Heredia-Rojas et al [2001] suggested that exposure to ELFMFs (60 Hz; 1.0, 1.5, and 2.0 mT) stimulates lymphocyte proliferation.…”
Section: Discussionmentioning
confidence: 83%